Experimental study and evaluation of mixing mechanism and performance in triple‐screw extruder. Issue 7 (1st December 2017) - Yang, Kunxiao; Xin, Chunling; Yu, Dongquan; Yan, Baorui; He, Yadong
Abstract: The mixing capacity of triangle‐arrayed triple‐screw extruder (TTSE) was evaluated through the extrusion of polypropylene/ethylene–propylene–diene monomer (PP/EPDM) at varying screw speeds. The micromorphology, mean residence time, melt flow rate (MFR), and mechanical properties of blends were measured for evaluation. Moreover, same experiments were applied on a twin‐screw extruder (TSE) for comparison. TTSE shows better mixing performance than TSE in comparison with micromorphology and mean residence time. But the high shear effect and temperature rising in TTSE promote the degradation of PP in blends which make the samples to have worse mechanical properties and higher MFR than those of TSE.